A Review of Sociological Theories and Interpretations of the Notion of «Lifestyle»: From Class Society to Postmodern - Елена Сергеевна Горбань (Journal of Economic Sociology, 2013)
The paper systematises key theoretical perspectives to the notion of lifestyle and the related empirical studies in socialsciences. It also reviews elements of this concept from different perspectives. The main aim is to find senses which researchers ascribe to the notion of lifestyle. The article embraces well-known texts devoted to lifestyle as well asless-known ones in Russia, including papers written in French. It pays equal attention to methodological issues and empirical research in order to describe the phenomenon of lifestyle in full detail. Special attention is given to the concept of lifestyle created by Pierre Bourdieu in the late XX century. His conception has many followers as well as a pleiad of critics; research by both groups is presented in the paper. Bourdieu demonstrated empirical evidence of consistency or rationality in people’s tastes, connecting consumer preferences with social class, upbringing and most importantly, habits. He argued that a person’s inclinations to any activity, hobby or even food preferences,can be explained by external factors and education level. However, the transition observed in the XXI century caused changes in societies and Bourdieu’s theory turns out to be irrelevant in some cases. The formation of a consumer society generated a new type of consciousness, including a new variety of lifestyle; postmodernism, which runs counter to logical expectations and consistency of choice implying confusion, eclecticism, plurality, and irrationality.